Political Conspiracy In Dan Brown's Deception Point (2001): A Sociological Approach - Ardy, Maria (2012)
The problem of this study is how political conspiracy reflected in Dan Brown's Deception Point novel. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the sociological approach. This study belongs to qualitative method. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel itself, meanwhile the secondary data sources are other materials related to the study. Both data are collected through library research and analyzed by descriptive analysis. Based on the analysis the researcher draws the following conclusions. First, based on the structural analysis, it is apparent that in this novel, Dan Brown wants to assert that some people use deception to reach their goal. Second, there is a close relationship between the novel, Deception Point, and American social realities in the late twentieth century. Third, America's social realities give contributions to create this story